Prepregs, printed circuit boards, and semiconductor devices

JP2026168577APending Publication Date: 2026-10-16SUMITOMO BAKELITE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025061763
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、良好な接続信頼性が得られるプリプレグを提供する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026168577000004
    Figure 2026168577000004
  • Figure 2026168577000001
    Figure 2026168577000001
  • Figure 2026168577000002
    Figure 2026168577000002
Patent Text Reader

Abstract

We provide a prepreg that offers good connection reliability. [Solution] The prepreg is made by impregnating a fibrous substrate with a thermosetting resin composition containing epoxy resin, a curing agent, and an inorganic filler, and the E2 / E1 ratio measured by the following procedure A is 0.70 or more and 0.85 or less, and the E3 / E2 ratio is 0.70 or more and 0.85 or less. (Procedure A) 12 μm copper foil is placed on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180 °C for 2 hours to obtain a laminate having copper foil on both sides with a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. A dynamic viscoelasticity measuring device is used to measure the cured product up to a temperature of 300 °C with a measurement frequency of 1 Hz and a heating rate of 5 °C / min, and the storage modulus at 30 °C is E1 (GPa), the storage modulus at 150 °C is E2 (GPa), and the storage modulus at 250 °C is E3 (GPa).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a prepreg, a printed wiring board, and a semiconductor device.

Background Art

[0002] In recent years, along with the demand for higher functionality of electronic devices, high-density integration and high-density mounting of electronic components have been progressing, and printed wiring boards and the like used therefor have seen expanding applications in miniaturization and higher density more than ever before. In the manufacture of such printed wiring boards and the like, a prepreg obtained by impregnating a fiber base material with a thermosetting resin composition is often used.

[0003] For example, Patent Document 1 discloses a thermosetting resin composition containing a phenol resin having an aliphatic hydrocarbon group with a specific number of carbon atoms, in order to obtain a prepreg with suppressed crack generation.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0005] Along with recent high-density integration and high-density mounting, higher connection reliability is required. Therefore, conventional printed wiring boards using prepregs as disclosed in Patent Document 1 tend to have a more significant difference in coefficient of linear expansion from semiconductor chips at high temperatures, leading to a tendency to generate warpage. Further, a method of highly filling an inorganic filler to reduce the difference in coefficient of linear expansion is known, but in this case, there were problems such as lowered adhesion. Accordingly, the present invention aims to achieve favorable connection reliability by lowering the coefficient of linear expansion while suppressing the blending amount of the inorganic filler.

Means for Solving the Problems

[0006] The inventors of this invention considered the above-mentioned problems and focused on the relationship between the storage modulus of prepreg and temperature. They then devised a new index for the relationship between the storage modulus and temperature and found that controlling this index is effective, thus completing the present invention.

[0007] According to the present invention, the following prepregs and related technologies are provided.

[0008] [1] A prepreg obtained by impregnating a fibrous substrate with a thermosetting resin composition comprising an epoxy resin, a curing agent, and an inorganic filler, A prepreg in which the E2 / E1 ratio measured by procedure A below is between 0.70 and 0.85, and the E3 / E2 ratio is between 0.70 and 0.85. (Procedure A) A 12 μm copper foil is placed on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. A dynamic viscoelasticity measuring device is used to measure the cured prepreg at a measurement frequency of 1 Hz and a heating rate of 5°C / min up to a temperature of 300°C, and the storage modulus at 30°C is E1 (GPa), the storage modulus at 150°C is E2 (GPa), and the storage modulus at 250°C is E3 (GPa). [2] [1] The prepreg described above, A prepreg in which the α1 / α2 ratio measured by the following procedure B is between 1.00 and 1.20. (Procedure B) A 12 μm copper foil is laid on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. For this cured product, the coefficient of thermal expansion at 150-200°C is α1 (ppm / K), and the coefficient of thermal expansion at 200-250°C is α2 (ppm / K). [3] [1] The prepreg described above, A prepreg in which the E3 measured in the above procedure A is between 15 GPa and 25 GPa. [4] [2] The prepreg described above, A prepreg in which the α2 measured in the above procedure B is between 3.8 ppm / K and 10 ppm / K. [5] [1] to [4] A prepreg described in any one of the above, The epoxy resin is a prepreg containing an esterified epoxy resin. [6] [1] to [5] A prepreg described in any one of the above, The curing agent is a prepreg comprising one or more selected from the group consisting of phenolic curing agents, cyanate curing agents, active ester curing agents, and benzoxazine curing agents. [7] [1] to [6] A prepreg described in any one of the above, A prepreg in which the inorganic filler content is 40% by mass or more and 85% by mass or less relative to the total solid content of the thermosetting resin composition. [8] [1] to [7] A prepreg described in any one of the above, A prepreg in which the fiber base material is one or more selected from glass fiber base material, polyamide resin fiber, polyester resin fiber, polyimide resin fiber, and fluororesin fiber. [9] [1] to [8] A prepreg described in any one of the above, A prepreg used to form an insulating layer on a printed circuit board.

[10] A printed circuit board comprising a cured prepreg according to any one of [1] to [9].

[11]

[10] A semiconductor device having semiconductor elements mounted on a printed circuit board. [Effects of the Invention]

[0009] The present invention provides a prepreg that offers good connection reliability. [Brief explanation of the drawing]

[0010] [Figure 1] This is a diagram showing dynamic viscoelasticity measurement charts of Example 1 and Comparative Example 1. [Modes for Carrying Out the Invention]

[0011] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.

[0012] In the present specification, the notation "a to b" in the description of numerical ranges means a or more and b or less, unless otherwise specified. For example, "1 to 5 mass%" means "1 mass% or more and 5 mass% or less".

[0013] In the present specification, the B-stage refers to a state where 5 to 40% of the resin composition is cured (semi-cured), and the C-stage is intended to mean a state where more than 90% of the resin composition is cured (fully cured). In addition, the degree of cure of the resin composition can be determined from the reaction rate measured by a differential scanning calorimeter.

[0014] <Prepreg> The prepreg of the present embodiment is obtained by impregnating a fiber base material with a thermosetting resin composition containing an epoxy resin, a curing agent, and an inorganic filler. The prepreg of the present embodiment is in a B-stage state. The prepreg of the present embodiment is fully cured, for example, by heating at 150 to 200°C for 60 to 240 minutes.

[0015] (Storage Modulus) In the prepreg of the present embodiment, E2 / E1 measured by the following Procedure A is 0.70 or more and 0.85 or less, and E3 / E2 is 0.70 or more and 0.85 or less.

[0016] (Procedure A) A 12 μm copper foil is placed on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. A dynamic viscoelasticity measuring device is used to measure the cured prepreg at a measurement frequency of 1 Hz and a heating rate of 5°C / min up to a temperature of 300°C, and the storage modulus at 30°C is E1 (GPa), the storage modulus at 150°C is E2 (GPa), and the storage modulus at 250°C is E3 (GPa).

[0017] In procedure A, the removal of the copper foil can be carried out using known methods, such as chemical etching using an etching solution, mechanical removal by polishing, removal of the copper foil by plasma etching using reactive gases such as fluorine-based or oxygen-based gases, and removal of the copper foil by laser processing. Among these, it is preferable to remove the copper foil by chemical etching using an etching solution. The copper foil is completely removed and can be confirmed by visual inspection.

[0018] This ensures good connection reliability. Specifically, E2 / E1 represents the storage modulus at relatively low temperatures, while E3 / E2 represents the storage modulus at relatively high temperatures. The fact that E2 / E1 is between 0.70 and 0.85, and E3 / E2 is between 0.70 and 0.85, indicates that the storage modulus does not change significantly from low to high temperatures. As a result, the prepreg of this embodiment maintains a relatively high storage modulus even at high temperatures, suppressing thermal expansion, reducing the increase in the coefficient of linear expansion, and effectively suppressing warping.

[0019] The E2 / E1 ratio is between 0.70 and 0.85, preferably between 0.75 and 0.85, and more preferably between 0.80 and 0.85.

[0020] E3 / E2 is between 0.70 and 0.85, preferably between 0.70 and 0.80, and more preferably between 0.71 and 0.78.

[0021] Furthermore, when the storage modulus at 250°C is E1 (GPa), E1 is preferably 25 GPa or more and 45 GPa or less, more preferably 28 GPa or more and 40 GPa or less, and even more preferably 30 GPa or more and 38 GPa or less.

[0022] Furthermore, when the storage modulus at 250°C is E2(GPa), E2 is preferably 20 GPa or more and 35 GPa or less, more preferably 22 GPa or more and 33 GPa or less, and even more preferably 25 GPa or more and 32 GPa or less.

[0023] Furthermore, when the storage modulus at 250°C is E3 (GPa), E3 is preferably 15 GPa or more and 25 GPa or less, more preferably 16 GPa or more and 25 GPa or less, and even more preferably 18 GPa or more and 24 GPa or less.

[0024] (Coefficient of linear expansion) Furthermore, the prepreg of this embodiment preferably has an α1 / α2 ratio of 1.00 or more and 1.20 or less, measured in the following procedure B, more preferably 1.05 or more and 1.18 or less, and even more preferably 1.08 or more and 1.16 or less. By setting α1 / α2 to be above the lower limit mentioned above, the increase in the coefficient of linear expansion at high temperatures can be suppressed, and warping can be effectively reduced. By keeping α1 / α2 below the above upper limit, fluctuations in the coefficient of thermal expansion can be suppressed.

[0025] (Procedure B) A 12 μm copper foil is laid on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. For this cured product, the coefficient of thermal expansion at 150-200°C is α1 (ppm / K), and the coefficient of thermal expansion at 200-250°C is α2 (ppm / K).

[0026] In procedure B, the copper foil can be removed using known methods, such as chemical etching with an etching solution, mechanical removal by polishing, removal of copper foil by plasma etching using reactive gases such as fluorine-based or oxygen-based gases, and removal of copper foil by laser processing. Among these, it is preferable to remove the copper foil by chemical etching with an etching solution. The copper foil is completely removed and can be confirmed visually.

[0027] When the coefficient of thermal expansion at 150-200°C is denoted as α1 (ppm / K), α1 is preferably 4.0 ppm / K or more and 11 ppm / K or less, preferably 4.2 ppm / K or more and 8.5 ppm / K or less, and preferably 4.5 ppm / K or more and 7.5 ppm / K or less.

[0028] When the coefficient of thermal expansion at 200-250°C is α2 (ppm / K), α2 is preferably 3.8 ppm / K or more and 10 ppm / K or less, preferably 4.0 ppm / K or more and 8.0 ppm / K or less, and preferably 4.2 ppm / K or more and 6.5 ppm / K or less.

[0029] Prepregs that satisfy the above-mentioned storage modulus and coefficient of linear expansion can be realized by appropriately adjusting and combining known materials and known methods. For example, this can be achieved by selecting raw materials for the thermosetting resin composition, adjusting the composition, selecting the shape and material of the fiber base material, fiber size, etc., and devising a prepreg manufacturing method.

[0030] (Thickness) The thickness of the prepreg can be set as appropriate depending on the application, but for example, it can be 0.05 to 10 mm.

[0031] The following describes the materials that make up the prepreg.

[0032] <Thermosetting resin composition> The content of the thermosetting resin composition in the prepreg is preferably 35 to 65% by mass in terms of solid content, more preferably 40 to 60% by mass, even more preferably 45 to 60% by mass, and most preferably 45 to 55% by mass.

[0033] (Epoxy resin) Specific examples of epoxy resins include, for example, biphenyl-type epoxy resins; bisphenol-type epoxy resins such as bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, bisphenol AD-type, and tetramethylbisphenol F-type epoxy resin; stilbene-type epoxy resins; novolac-type epoxy resins such as phenol novolac-type epoxy resin and cresol novolac-type epoxy resin; polyfunctional epoxy resins such as triphenyl-type epoxy resins, including triphenyl-type epoxy resins exemplified by triphenolmethane-type epoxy resin and alkyl-modified triphenolmethane-type epoxy resin; phenol aralkyl-type epoxy resins having a phenylene skeleton, naphthol aralkyl-type epoxy resins having a phenylene skeleton, and phenol aralkyl-type epoxy resins having a biphenylene skeleton (biphenyl aralkyl Examples include phenol aralkyl epoxy resins such as naphthol aralkyl epoxy resins having a biphenylene skeleton; naphthol epoxy resins such as dihydroxynaphthalene epoxy resins and epoxy resins obtained by glycidyl etherification of a dimer of dihydroxynaphthalene; triazine core-containing epoxy resins such as triglycidyl isocyanurate and monoallyl diglycidyl isocyanurate; bridged cyclic hydrocarbon compound-modified phenol epoxy resins such as dicyclopentadiene-modified phenol epoxy resins; brominated epoxy resins such as brominated bisphenol A and brominated phenol novolac; tris(hydroxyphenyl)methane-type epoxy resins; and esterified epoxy resins in which some or all of the epoxy groups of an epoxy resin are esterified. One of these epoxy resins may be used alone, or two or more different types may be used in combination. In particular, it is preferable to include an esterified epoxy resin, and it is even more preferable to use an esterified epoxy resin in combination with other epoxy resins.

[0034] (Esterified epoxy resin) Esterified epoxy resins have a high molecular weight and can have a structure in which some or all of the polar groups, such as hydroxyl groups that exhibit water absorption, are capped with hydrophobic groups. The mass-average molecular weight Mw of this esterified epoxy resin is, for example, 5,000 to 200,000, preferably 10,000 to 100,000, and more preferably 20,000 to 80,000. Such an esterified epoxy resin can suppress warping at high temperatures.

[0035] Furthermore, the esterified epoxy resin may include, for example, a compound having an epoxy group at its terminal end, represented by the following formula (1).

[0036] [ka]

[0037] (In formula (1) above, A includes the structure represented by formula (2) above, R 1 and R 2 These elements may be different from each other and are hydrogen atoms or structures represented by the above formula (3). However, R 1 and R 2 At least one of the above is a group represented by formula (3). 3 At least 5 mol% of the compound consists of aliphatic carbonyl groups or aromatic carbonyl groups having 1 to 10 carbon atoms, with the remainder being hydrogen atoms, where n is the average value of the repeating number and is between 5 and 500. In formula (2) above, X 1 R is a directly bonded, divalent hydrocarbon group having 1 to 13 carbon atoms, selected from -O-, -S-, -SO2-, -C(CF3)2- and -CO-. 4 ~R 11 Each of these groups is independently selected from a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkenyl group having 1 to 12 carbon atoms, and an alkynyl group having 1 to 12 carbon atoms.

[0038] The structure represented by formula (2) above is, for example, the structure represented by formula (4) or formula (5) below.

[0039] [ka]

[0040] The above-mentioned esterified epoxy resin can be obtained by reacting an epoxy resin such as a bifunctional epoxy resin, an ester compound such as a diester compound, a catalyst, and a solvent under a nitrogen gas atmosphere, under predetermined reaction time and temperature conditions. Examples of bifunctional epoxy resins include epoxy resins obtained by condensing a bisphenol compound with an epihalohydrin by a known method. Examples of diester compounds include diacetoxy compounds. Any compound that has catalytic activity to promote the reaction between epoxy groups and ester groups can be used as a catalyst. Examples include tertiary amines, cyclic amines, imidazoles, organophosphorus compounds, and quaternary ammonium salts. Examples of commercially available esterified epoxy resins include "YL7899," "YL7891," and "YL7903" manufactured by Mitsubishi Chemical Corporation.

[0041] The epoxy resin content is preferably 5 to 50% by mass, more preferably 10 to 40% by mass, and even more preferably 15 to 25% by mass, relative to the solid content of the thermosetting resin composition.

[0042] The lower limit of the esterified epoxy resin content is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, relative to the total amount of epoxy resin. This suppresses the increase in the storage modulus of the cured product of the thermosetting resin composition when heated. On the other hand, the upper limit of the esterified epoxy resin content is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 65% ​​by mass or less, relative to the total amount of epoxy resin. This allows for a balance with other physical properties.

[0043] (Hardening agent) The curing agent is not particularly limited as long as it reacts with the epoxy resin. Specific examples of curing agents include polyaddition curing agents, catalytic curing agents, and condensation curing agents.

[0044] Examples of curing agents include amine-based curing agents, guanidine-based curing agents, imidazole-based curing agents, phenol-based curing agents, naphthol-based curing agents, acid anhydride-based curing agents or their epoxy adducts or microencapsulated forms, active ester-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, etc. One or more of these can be used.

[0045] Phenolic curing agents specifically include one or more selected from the following: novolac-type phenolic resins such as phenol novolac resins, cresol novolac resins, naphthol novolac resins, aminotriazine novolac resins, and trisphenylmethane-type phenol novolac resins; modified phenolic resins such as terpene-modified phenolic resins and dicyclopentadiene-modified phenolic resins; aralkyl-type resins such as phenol aralkyl resins having a phenylene skeleton and / or biphenylene skeleton, and naphthol aralkyl resins having a phenylene skeleton and / or biphenylene skeleton; bisphenol compounds such as bisphenol A and bisphenol F; and resol-type phenolic resins.

[0046] The lower limit of the hydroxyl group equivalent of the curing agent is, for example, 200 g / eq or more, preferably 210 g / eq or more, and more preferably 220 g / eq or more. This allows for the acquisition of an optimal crosslinking density. On the other hand, the upper limit of the hydroxyl equivalent of the curing agent is not particularly limited, but may be, for example, 700 g / eq or less, 600 g / eq or less, or 500 g / eq or less. This can improve the strength of the cured product of the thermosetting resin composition.

[0047] The amount of the curing agent can be appropriately set according to the number of functional groups in the epoxy resin. Furthermore, when a phenolic curing agent is used as the curing agent, the content ratio of epoxy resin to phenolic curing agent can be such that the equivalent ratio (EP) / (OH) of the total number of epoxy groups (EP) of the epoxy resin to the total number of phenolic hydroxyl groups (OH) of the phenolic curing agent is, for example, 0.8 or more and 1.5 or less.

[0048] (Inorganic filler) Inorganic fillers are used to enhance the mechanical strength of prepregs, or to impart properties such as heat resistance and flame retardancy, depending on the application of the prepreg.

[0049] Examples of inorganic fillers include silicates such as talc, calcined clay, uncalcined clay, mica, and glass; oxides such as titanium dioxide, alumina, boehmite, and silica; carbonates such as calcium carbonate, magnesium carbonate, and hydrotalcite; hydroxides such as aluminum hydroxide, magnesium hydroxide, and calcium hydroxide; sulfates or sulfites such as barium sulfate, calcium sulfate, and calcium sulfite; borates such as zinc borate, barium metaborate, aluminum borate, calcium borate, and sodium borate; nitrides such as aluminum nitride, boron nitride, silicon nitride, and carbon nitride; and titanates such as strontium titanate and barium titanate. These may be used individually or in combination of two or more.

[0050] The lower limit of the inorganic filler content is not particularly limited relative to 100% by mass of the total solids content of the thermosetting resin composition, but for example, 40% by mass or more is preferred, 50% by mass or more is more preferred, and 60% by mass or more is even more preferred. This makes it possible to achieve particularly low thermal expansion of the cured resin film. On the other hand, the upper limit of the inorganic filler content is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, relative to 100% by mass of the total solids content of the thermosetting resin composition, in order to obtain good adhesion. This improves the processability of the cured resin film.

[0051] (Curing accelerator) The thermosetting resin composition of this embodiment may contain, for example, a curing accelerator. This can improve the curability of the thermosetting resin composition. As a curing accelerator, any agent that accelerates the curing reaction of a thermosetting resin can be used, and the type is not particularly limited. In this embodiment, examples of curing accelerators include organometallic salts such as zinc naphthenate, cobalt naphthenate, tin octate, cobalt octate, zinc octate, bisacetylacetonate cobalt(II), trisacetylacetonate cobalt(III), tertiary amines such as triethylamine, tributylamine, and diazabicyclo[2,2,2]octane, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-ethyl-4-ethylimidazole. It may contain one or more selected from imidazoles such as 2-phenyl-4-ethylimidazole, 2-phenyl-4-methyl-5-hydroxyimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2-phenyl-4,5-dihydroxyimidazole; phenol compounds such as phenol, bisphenol A, and nonylphenol; organic acids such as acetic acid, benzoic acid, salicylic acid, and p-toluenesulfonic acid; and onium salt compounds.

[0052] (Cyanate resin) The thermosetting resin composition of this embodiment may further contain a cyanate resin. Cyanate resins are resins having cyanate groups (-O-CN) in their molecules, and resins having two or more cyanate groups in their molecules can be used. Such cyanate resins are not particularly limited, but for example, they can be obtained by reacting cyanide compounds with phenols or naphthols and prepolymerizing them by heating or other methods as needed. Commercially available products prepared in this manner can also be used. By using cyanate resin, the coefficient of thermal expansion of the cured resin film can be reduced. Furthermore, the electrical properties (low dielectric constant, low dielectric loss tangent), mechanical strength, etc. of the cured resin film can be improved.

[0053] Examples of cyanate resins include novolac-type cyanate resins; bisphenol-type cyanate resins such as bisphenol A-type cyanate resins, bisphenol E-type cyanate resins, and tetramethylbisphenol F-type cyanate resins; naphthol aralkyl-type cyanate resins obtained by the reaction of naphthol aralkyl-type phenol resins with cyanide halides; dicyclopentadiene-type cyanate resins; and biphenylalkyl-type cyanate resins. Among these, novolac-type cyanate resins and naphthol aralkyl-type cyanate resins are preferred, with novolac-type cyanate resins being more preferred.

[0054] The lower limit of the cyanate resin content is preferably, for example, 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on 100% by mass of the total solids content of the thermosetting resin composition. This makes it possible to achieve low linear expansion and high modulus of elasticity of the cured resin film. On the other hand, the upper limit of the cyanate resin content is not particularly limited, but is preferably, for example, 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on 100% by mass of the total solids content of the thermosetting resin composition. This makes it possible to improve heat resistance and moisture resistance. Furthermore, if the cyanate resin content is within the above range, the storage modulus E' of the cured resin film can be further improved.

[0055] (thermoplastic resin) The thermosetting resin composition of this embodiment may also contain a thermoplastic resin. Examples of the thermoplastic resins mentioned above include acrylic resin, methacrylic resin, polyvinyl acetal resin, thermoplastic polyimide resin, polyamide resin, polyamide-imide resin, polyphenylene oxide resin, polyethersulfone resin, polyester resin, polyethylene resin, polystyrene resin, polysulfone resin, polybutadiene resin, and ABS resin. One of these thermoplastic resins may be used alone, or two or more with different mass-average molecular weights may be used in combination, or one or more types may be used in combination with their prepolymers.

[0056] The content of thermoplastic resin is not particularly limited, but is preferably 0.5% by mass or more and 40% by mass or less, and more preferably 1% by mass or more and 20% by mass or less, relative to the entire thermosetting resin composition excluding inorganic fillers.

[0057] (Surfactants) The surfactant has the advantage of suppressing the repulsion of the thermosetting resin composition and reducing the occurrence of surface defects, for example, during the manufacturing of prepregs (when impregnating a fiber substrate with a thermosetting resin composition). Examples of surfactants include nonionic surfactants, anionic surfactants, cationic surfactants, silicone surfactants, and UV-curing surfactants. Examples of commercially available silicone-based surfactants include BYK302, BYK307, BYK333, BYK341, BYK345, BYK346, BYK347, BYK348, and BYK-361N (manufactured by Bic Chemie Japan).

[0058] (Coupling agent) The resin composition of this embodiment may also contain a coupling agent. This suppresses aggregation of the inorganic filler and allows for good fluidity.

[0059] As coupling agents, known coupling agents such as various silane compounds including epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, and vinylsilane, as well as titanium compounds, aluminum chelates, and aluminum / zirconium compounds can be used.

[0060] (others) Furthermore, the thermosetting resin composition may contain other known compounds depending on the application. Examples of known compounds include additives such as elastomers, pigments, flame retardants, and adhesion enhancers. The composition may contain only one of these, or two or more.

[0061] <Method for producing thermosetting resin compositions> Next, a method for producing the resin composition of this embodiment will be described. The method for producing the resin composition of this embodiment is not particularly limited, but for example, if the thermosetting component and other arbitrary components are liquid, they are mixed by stirring with a stirring spring using a three-way motor or the like. If the thermosetting component and other arbitrary components are solid, they are mixed using a mixer or the like, and then kneaded by melting and heating at about 90 to 120°C using a heated kneader, heated roll, or extruder or the like. Next, the resulting kneaded material is cooled and pulverized to obtain a powdered or granular resin composition. The resin composition may be compressed into tablets after pulverization as needed, or it may be made into a sheet by, for example, vacuum lamination or compression molding after pulverization.

[0062] Alternatively, for example, a varnish-like resin composition may be prepared by dissolving, mixing, and stirring thermosetting components and other arbitrary components in a solvent using various mixers such as ultrasonic dispersion, high-pressure impact dispersion, high-speed rotation dispersion, bead mill, high-speed shear dispersion, or rotation-orbit dispersion.

[0063] <Textile base material> The prepregs of this embodiment include glass fiber substrates such as glass fiber fabrics and glass nonwoven fabrics, and inorganic fiber substrates such as fabrics or nonwoven fabrics composed of one or more selected from carbon fibers, graphite fibers, and silicon carbide fibers; and organic fiber substrates composed of organic fibers such as aromatic polyamide-imide resins, polyamide resins, aromatic polyester resins, polyester resins, polyimide resins, and fluororesins.

[0064] Examples of the above-mentioned glass fibers include glass fibers formed from one or more types of glass selected from E glass, S glass, D glass, T glass, NE glass, UT glass, L glass, HP glass, and quartz glass.

[0065] The shape of the fibrous base material is not particularly limited and may include woven fabric, nonwoven fabric, rawhide, chopped strand mat, surfacing mat, etc. However, it is preferable to use glass cloth, which is a woven fabric type, from the viewpoint of mechanical strength and dimensional stability. There are no particular restrictions on the diameter of the glass filament or the yarn used in the glass cloth, and they can be selected according to the thickness of the prepreg. However, from the standpoint of mechanical strength and dimensional stability, the filament diameter is preferably 4.5 μm or larger, and the yarn Tex count is preferably 5 g / km or larger.

[0066] The thickness of the fiber substrate is not particularly limited, but is preferably 10 μm to 400 μm, more preferably 20 μm to 300 μm, and even more preferably 40 μm to 200 μm. By using a fiber substrate with such a thickness, handling during prepreg manufacturing can be further improved.

[0067] <Prepreg manufacturing method> As a method for manufacturing prepregs, there are no particular limitations on the method of impregnating a fiber substrate with a thermosetting resin composition. Examples include: preparing a resin varnish by dissolving a thermosetting resin composition in a solvent and immersing the fiber substrate in the resin varnish; applying the resin varnish to the fiber substrate using various coaters; spraying the resin varnish onto the fiber substrate; and laminating both sides of the fiber substrate with a resin film made of a thermosetting resin composition.

[0068] In a varnish-like thermosetting resin composition, the solid content may preferably be 30% to 80% by mass, and more preferably 40% to 70% by mass. This results in a resin composition with excellent workability and impregnation properties. Furthermore, if the thermosetting resin composition is in the form of a varnish, it may be used as is without dilution if the thermosetting resin is in the form of a liquid, or it may be diluted with a known solvent if the thermosetting resin is in the form of a solid.

[0069] Next, the fiber substrate impregnated with the thermosetting resin composition is heated to stage B. The heating conditions are not particularly limited, but may be 70°C to 180°C for 1 to 60 minutes.

[0070] In this way, the prepreg of this embodiment can be obtained.

[0071] <Printed wiring board> The printed circuit board of this embodiment includes an insulating layer made of the cured prepreg described above. For example, it can be used as a build-up layer in a normal printed circuit board, a build-up layer in a printed circuit board without a core layer, a build-up layer in a coreless substrate used in PLP, a build-up layer in a MIS substrate, etc. Such an insulating layer constituting a build-up layer can also be suitably used as a build-up layer in a large-area printed circuit board used to create multiple semiconductor packages at once.

[0072] Although embodiments of the present invention have been described above, these are merely examples, and various other configurations can be adopted. Furthermore, the present invention is not limited to the embodiments described above, and modifications, improvements, etc., within the scope of achieving the objectives of the present invention are included. [Examples]

[0073] Embodiments of the present invention will be described in detail based on examples and comparative examples. However, the present invention is not limited to these examples.

[0074] (Preparation of thermosetting resin composition) For each example and comparative example, a varnish-like thermosetting resin composition (resin varnish P) was prepared. First, each component was dissolved or dispersed according to the solid content ratio shown in Table 1, and the non-volatile content was adjusted with methyl ethyl ketone to 70% by weight. The mixture was then stirred using a high-speed stirring device to prepare resin varnish P. The numerical values ​​in Table 1 indicating the proportion of each component represent the proportion (by weight) of each component relative to the total solid content of the thermosetting resin composition.

[0075] The details of the raw materials for each component in Table 1 are as follows. (thermosetting resin) • Epoxy resin 1: Naphthalene-modified novolac type epoxy resin with epoxy equivalent weight of 250 g / eq and a softening point of 58°C (DIC Corporation, HP-5000) • Epoxy resin 2: Epoxy equivalent weight 487g / eq, liquid epoxy resin (manufactured by Mitsubishi Chemical Corporation, YX7105) • Epoxy resin 3: Epoxy equivalent weight 1124 g / eq, liquid epoxy resin (manufactured by Mitsubishi Chemical Corporation, YX7110) • Epoxy resin 4: Epoxy equivalent weight 7000 g / eq, esterified epoxy resin (manufactured by Mitsubishi Chemical Corporation, YL7899)

[0076] (Hardening agent) • Hardener 1: Novolac-type cyanate resin (Arcsaada Corporation, PT-30)

[0077] (Inorganic filler) • Inorganic filler 1: Silica particles (Admatex, SC4050, average particle size 1.1 μm)

[0078] (Curing accelerator) • Curing accelerator 1: Imidazole compound (2-phenyl-4-methyl-5-hydroxyimidazole, manufactured by Shikoku Chemicals Co., Ltd., Cureazole 2P4MHz)

[0079] (2) Preparation of prepregs Each varnish obtained in (1) above was impregnated with the fibrous substrate shown in Table 1. The fibrous substrate was then removed and dried in a hot air dryer at 150°C for 2 minutes to obtain a prepreg in which a resin composition was impregnated into the glass cloth in an amount that would be 100 μm thick after press molding.

[0080] (Storage modulus) Using the prepreg obtained in (2) above, the storage moduli E1, E2, and E3 were determined according to the following procedure A. (Procedure A) A 12 μm copper foil (3EC-M3-VLP foil, manufactured by Mitsui Mining & Smelting Co., Ltd.) was laid on both sides of the prepreg, and the material was heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides was completely removed from the laminate to obtain a cured prepreg. The cured material was measured using a dynamic viscoelasticity measuring device with a measurement frequency of 1 Hz and a heating rate of 5°C / min, up to a temperature of 300°C. The storage modulus at 30°C was defined as E1(GPa), the storage modulus at 150°C as E2(GPa), and the storage modulus at 250°C as E3(GPa).

[0081] The conditions for the measurement were as follows: • Measurement sample: 5mm x 50mm test piece • Measurement equipment: A dynamic viscoelasticity measuring device, the "DMA7100" manufactured by Hitachi High-Tech Corporation, was used.

[0082] Furthermore, as an example, the dynamic viscoelasticity measurement results for Example 1 and Comparative Example 1 are shown in Figure 1. In Figure 1, the vertical axis shows the storage modulus (GPa) and the horizontal axis shows the temperature (°C).

[0083] (Coefficient of thermal expansion) Using the prepreg obtained in (2) above, the thermal expansion coefficients α1 and α2 were determined according to the following procedure B. (Procedure B) A 12 μm copper foil (3EC-M3-VLP foil, manufactured by Mitsui Mining & Smelting Co., Ltd.) was laid on both sides of the prepreg, and the material was heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides was completely removed from the laminate to obtain a cured prepreg. For this cured material, the coefficient of thermal expansion at 150-200°C was defined as α1 (ppm / K), and the coefficient of thermal expansion at 200-250°C was defined as α2 (ppm / K).

[0084] The conditions for the measurement were as follows: • Measurement sample: 4mm x 20mm test piece • Measurement equipment: Thermomechanical analyzer (Hitachi High-Tech Corporation, TMA7100). The Hitachi High-Tech Corporation "DMA7100" was used.

[0085] (3) Fabrication of printed circuit board A laminate with copper foil on both sides and a thickness of 0.1 mm was obtained by layering 12 μm copper foil (3EC-M3-VLP foil, manufactured by Mitsui Mining & Smelting Co., Ltd.) on both sides of the 100 μm thick prepreg obtained in (2) above, and then heat-pressure molding it at a pressure of 3 MPa and a temperature of 180°C for 2 hours. After roughening the copper foil layer on the surface of the laminate by approximately 1 μm, a φ80 μm through-hole for interlayer connection was formed using a carbon dioxide laser. Next, the laminate was immersed in a 60°C swelling solution (Atotec Japan, Sweep Dip Securigant P) for 5 minutes, and then immersed in an 80°C potassium permanganate aqueous solution (Atotec Japan, Concentrate Compact CP) for 2 minutes, after which it was neutralized and desmeared inside the through-hole. Next, electroless copper plating was performed to a thickness of 0.5 μm, a resist layer for electrolytic copper plating to a thickness of 18 μm was formed, a pattern copper plating was performed, and post-curing was performed by heating at a temperature of 150°C for 30 minutes. Then, the plating resist was peeled off and the entire surface was flash etched to form a pattern with L / S = 15 / 15 μm.

[0086] (4) Fabrication of semiconductor devices The resulting printed circuit board (printed circuit board after the circuit pattern was formed) was laminated and cured with build-up material (Sumitomo Bakelite Co., Ltd., BLA-3700GS), and the circuit was fabricated using the semi-additive method. A 10mm x 10mm x 100μm thick semiconductor element with solder bumps was mounted on top, sealed with underfill (Sumitomo Bakelite Co., Ltd., CRP-4160G), and cured at 150°C for 2 hours. Finally, it was diced into 15mm x 15mm pieces to fabricate a semiconductor device.

[0087] (5) Evaluation The following measurements and evaluations were performed using the obtained semiconductor device.

[0088] ·evaluation The warpage of semiconductor devices at 260°C was evaluated using a temperature-variable laser three-dimensional measuring machine (Hitachi Technology & Services, model LS220-MT100MT50). The semiconductor device was placed face down in the sample chamber of the measuring machine, and the displacement in the height direction was measured. The value with the largest difference in displacement was defined as the amount of warpage, and it was evaluated according to the following criteria. (standard) A: Warpage is less than 30 μm B: Warpage of 30 μm or more and less than 50 μm C: Warpage of 50 μm or more

[0089] [Table 1]

[0090] In Table 1, "phr" stands for per hundred resin, and represents the content (parts by mass) when the total amount of epoxy resin and hardener excluding inorganic fillers is set to 100 parts by mass.

Claims

1. A prepreg obtained by impregnating a fibrous substrate with a thermosetting resin composition containing epoxy resin, a curing agent, and an inorganic filler, A prepreg in which the E2 / E1 ratio measured by the following procedure A is between 0.70 and 0.85, and the E3 / E2 ratio is between 0.70 and 0.

85. (Procedure A) A 12 μm copper foil is placed on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. A dynamic viscoelasticity measuring device is used to measure the cured prepreg at a measurement frequency of 1 Hz and a heating rate of 5°C / min up to a temperature of 300°C, and the storage modulus at 30°C is E1 (GPA), the storage modulus at 150°C is E2 (GPA), and the storage modulus at 250°C is E3 (GPA).

2. The prepreg according to claim 1, A prepreg in which the α1 / α2 ratio measured by the following procedure B is between 1.00 and 1.

20. (Procedure B) A 12 μm copper foil is placed on both sides of the prepreg, and it is heated and pressurized at a pressure of 3 MPa and a temperature of 180°C for 2 hours to obtain a laminate with copper foil on both sides and a thickness of 0.1 mm. Next, the copper foil on both sides is removed from the laminate to obtain a cured prepreg. For this cured product, the coefficient of thermal expansion at 150 to 200°C is α1 (ppm / K), and the coefficient of thermal expansion at 200 to 250°C is α2 (ppm / K).

3. The prepreg according to claim 1, A prepreg in which the E3 measured in the above procedure A is 15 GPa or more and 25 GPa or less.

4. The prepreg according to claim 2, A prepreg in which the α2 measured in the above procedure B is 3.8 ppm / K or more and 10 ppm / K or less.

5. A prepreg according to any one of claims 1 to 4, The epoxy resin is a prepreg containing an esterified epoxy resin.

6. A prepreg according to any one of claims 1 to 4, The curing agent is a prepreg comprising one or more selected from the group consisting of phenolic curing agents, cyanate curing agents, active ester curing agents, and benzoxazine curing agents.

7. A prepreg according to any one of claims 1 to 4, A prepreg in which the inorganic filler content is 40% by mass or more and 85% by mass or less relative to the total solid content of the thermosetting resin composition.

8. A prepreg according to any one of claims 1 to 4, A prepreg in which the fiber base material is one or more selected from glass fiber base material, polyamide resin fiber, polyester resin fiber, polyimide resin fiber, and fluororesin fiber.

9. A prepreg according to any one of claims 1 to 4, A prepreg used to form an insulating layer on a printed circuit board.

10. A printed circuit board comprising a cured prepreg according to any one of claims 1 to 4.

11. A semiconductor device in which a semiconductor element is mounted on a printed wiring board according to claim 10.

Citation Information

Patent Citations

  • Thermosetting resin composition, prepreg, resin-coated metal foil, laminate, printed wiring board, and semiconductor package

    WO2019189811A1